22.4k views
21 votes
Please solve this asap​

Please solve this asap​-example-1

1 Answer

6 votes

Let
\vec u and
\vec v be the vectors, and let
x=\|\vec u\|=\|\vec v\| be their common magnitude.

The resultant
\vec u + \vec v is
\sqrt 2 times larger in magnitude than either vector alone, so
\|\vec u+\vec v\| = \sqrt2\,x.

Recall the dot product identity


\vec a \cdot \vec b = \|\vec a\| \|\vec b\| \cos(\theta)

where
\theta is the angle between the vectors
\vec a and
\vec b. In the special case of
\vec a=\vec b, we get


\vec a \cdot \vec a = \|\vec a\|^2 \cos(0^\circ) \implies \|\vec a\| = √(\vec a\cdot\vec a)

Now, to get the angle between
\vec u and
\vec v, we have


\vec u \cdot \vec v = \|\vec u\| \|\vec v\| \cos(\theta) \implies \cos(\theta) = (\vec u \cdot \vec v)/(x^2)

To compute the dot product, we take the dot product of the resultant with itself.


(\vec u+\vec v) \cdot (\vec u + \vec v) = \|\vec u + \vec v\|^2

Solve for
\vec u\cdot\vec v.


(\vec u\cdot\vec u) + 2(\vec u\cdot\vec v) + (\vec v\cdot\vec v) = \|\vec u + \vec v\|^2


\|\vec u\|^2 + 2(\vec u\cdot \vec v) + \|\vec v\|^2 = \|\vec u+\vec v\|^2


x^2 + 2(\vec u \cdot \vec v) + x^2 = (\sqrt2\,x)^2


2(\vec u\cdot\vec v) + 2x^2 = 2x^2


2(\vec u\cdot\vec v) = 0


\vec u\cdot\vec v = 0

Since their dot product is zero,
\vec u and
\vec v are perpendicular, so
\theta=90^\circ.

User Carlos Cordoba
by
6.8k points